La Reparación Integral y las Víctimas del Conflicto Armado en el Marco de la Ley 1448 de 2011 (2022)
Throughout the history of Colombia, the internal armed conflict has been the issue that has gained the most relevance in recent decades at the different levels of the National Government, and Colombians have not been oblivious to this phenomenon; In this way, the study objective of this monograph focuses on developing an analysis of Law 1448 of 2011 from the following actions: reviewing its historical component; stressing chronologically, with notable events that gave rise to its creation, the expectations during its approval and how the procedure has been defined and applied since its entry into force; finally, reviewing both the regulatory component and the jurisprudence. This document tries to establish and explain concepts that have been defined by the high courts regarding comprehensive reparation in Colombia under the legal framework of Law 1448 of 2011, and its distinctions compared to other jurisdictions.